2015
DOI: 10.1186/s12864-015-1646-6
|View full text |Cite
|
Sign up to set email alerts
|

Early life microbial colonization of the gut and intestinal development differ between genetically divergent broiler lines

Abstract: BackgroundHost genetic makeup plays a role in early gut microbial colonization and immune programming. Interactions between gut microbiota and host cells of the mucosal layer are of paramount importance for a proper development of host defence mechanisms. For different livestock species, it has already been shown that particular genotypes have increased susceptibilities towards disease causing pathogens.The objective of this study was to investigate the impact of genotypic variation on both early microbial col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 78 publications
5
105
0
1
Order By: Relevance
“…Regarding the changes in microbiota during feed restriction, our data revealed that lactobacilli, a group recognized as autochthonous in the gastrointestinal tract (Lunedo et al, ), were decreased by both feed restriction programmes in the ileum of the broilers. Members of this group produce lactic acid which inhibits pathogens proliferation and adhesion (Schokker et al, ) and rigidifies the intercellular junctions, protecting the epithelium (Lutgendorff, Akkermans, & Soderholm, ). This group is important to maintain the stability of the intestinal microbial ecosystem, notwithstanding in great counts could increase intestinal inflammation and affects animal performance (Torok, Allison, Percy, Ophel‐Keller, & Hughes, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the changes in microbiota during feed restriction, our data revealed that lactobacilli, a group recognized as autochthonous in the gastrointestinal tract (Lunedo et al, ), were decreased by both feed restriction programmes in the ileum of the broilers. Members of this group produce lactic acid which inhibits pathogens proliferation and adhesion (Schokker et al, ) and rigidifies the intercellular junctions, protecting the epithelium (Lutgendorff, Akkermans, & Soderholm, ). This group is important to maintain the stability of the intestinal microbial ecosystem, notwithstanding in great counts could increase intestinal inflammation and affects animal performance (Torok, Allison, Percy, Ophel‐Keller, & Hughes, ).…”
Section: Discussionmentioning
confidence: 99%
“…Members of this group produce lactic acid which inhibits pathogens proliferation and adhesion (Schokker et al, 2015) and rigidifies the intercellular junctions, protecting the epithelium (Lutgendorff, Akkermans, & Soderholm, 2008). This group is important to maintain the stability of the intestinal microbial ecosystem, notwithstanding in great counts could increase intestinal inflammation and affects animal performance (Torok, Allison, Percy, Ophel-Keller, & Hughes, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This decline was associated with increased abundance of Lactobacillus which replaced Enterobacteriaceae as the dominant taxa by 14 d.p.h (27). Schokker et al (28) described a faster transition to higher abundance of Lactobacillus. The day-old microbiome was dominated by Enterococcaceae with a high proportion of Escherichia sequences and Lactobacillus present but in very low numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Kaakoush et al (2014), who studied the microbiota of chickens from two farms, assigned them to four enterotypes dominated by varies phyla. Many factors influence the composition of the chicken microbiota; the most substantial factors are the chicken breeds, bird age, and farming practices (Kaakoush et al, 2014;Oakley, Buhr, et al, 2014;Schokker et al, 2015;Thibodeau et al, 2015).…”
Section: Introductionmentioning
confidence: 99%